Functional and structural insights into the multicopper oxidase MmcO from Mycobacterium tuberculosis: implications for drug targeting - Liu, Dafeng; Yu, Feng; Luo, Yihan; Hanate, Ayitunihe (Frontiers in Chemistry, 2025)
Mycobacterium tuberculosis (Mtb) is a significant and highly pathogenic intracellular microorganism responsible for tuberculosis (TB). The global TB crisis has been exacerbated by the emergence and spread of multidrug-resistant Mtb strains, resulting in elevated mortality rates. Mtb MmcO exhibits scavenging activity against reactive oxygen species (ROS), thereby supporting Mtb survival. However, the molecular mechanism underlying MmcO function remains poorly understood. Herein, the hydrodynamic radius of MmcO was determined to be 5.9 ± 0.3 nm. A structural model of MmcO was predicted using AlphaFold2 and subsequently evaluated for accuracy using a Ramachandran plot and ProSA analysis. Site-directed mutagenesis revealed that substitutions H120A, H122A, H161A, or H163A nearly abolished the activity, while mutations H120R, H122R, H161R, or H163R led to minor alterations in the activity. The addition of Triton X-100 or Ca2+ significantly enhanced MmcO activity, whereas EDTA or other metal ions markedly inhibited its activity to varying extents. MmcO, a multicopper oxidase, plays a role in maintaining redox homeostasis in Mtb, a function critical for bacterial survival in host macrophages. Our study reveals that Cu2+ is essential for enzymatic activity, while Ni2+, Mn2+, and Zn2+ inhibit function, likely due to improper metal coordination. Given its importance in oxidative stress resistance, MmcO presents a promising drug target for Mtb therapy. Therefore, this study offers valuable insights for developing novel therapeutic agents targeting Mtb.